OPTIMALISASI CYCLE TIME ALAT ANGKUT DUMP TRUCK CGE37084R UNTUK PENCAPAIAN TARGET PRODUKTIVITAS PENGANGKUTAN BATUBARA DI PT WAHANA BANDHAWA KENCANA SITE PT BARA ALAM UTAMA LAHAT, SUMATERA SELATAN - Kemas Moh. Ade Isnaeni; Sarmila Tri Ayu; Sepriadi (Bajang Institute, 2023)
PT Wahana Bandhawa Kencana is a mining company operating as a contractor. Mining activities include a set of overburden and coal getting activities. In mining activities, produktivity target plays an important role in a mining company, so it is necessary to figure out the cycle time of used equipment. The method of this research was quantitative and observation on field condition was also conducted. The objectives of this research was to determine the cycle time, productivity and efforts to optimize the cycle time as well as the cycle time and produktivity after conducting optimization. From the field observation and calculation, the actual cycle time average CGE37084R dump truck was 39.80 minutes while the ideal one was 25.33 minutes, the produktivity was 26.31 tonnes/hour. The optimization efforts conducted to achieve the productivity target was optimizing the actual cycle time from 39.80 minutes to 38.95 minutes. With the optimized cycle time, the obtained produktivity was 26.88 tonnes/hour. The cycle time optimization was implemented by widening the front area and leveling road on the hauling road so that it could optimize the cycle time from 39.80 minutes to 38.95 minutes. The decreasing obstacle time was 0.85 minutes and the productivity increased as much as 0.75 tonnes/hour.